Interaksi Islam dan Budaya Lokal Studi Kasus Tradisi Pernikahan Ala Betawi - Faiz Fikri Al Fahmi; Najwa Aprilia Putri; Qonita Luthfiah Mandayni; Annajwa Annajwa; Muhammat Iqbal Ritongah; Muhammad Husein Kurtucy (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to understand the role and significance of the Palang Pintu tradition in Betawi wedding ceremonies and its impact amidst modernization and globalization. Utilizing a qualitative research method with a literature study approach, the research relies on secondary data sources such as books, journal articles, documents, and related research reports. Data analysis was conducted using content analysis techniques to identify the main themes and categories from the collected data. The results show that the Palang Pintu tradition remains relevant and valued by the Betawi community, both natives and immigrants. This tradition is seen as an important way to preserve culture, protect families, and serve as a symbol of respect in wedding ceremonies. These findings highlight the importance of maintaining local traditions as an integral part of cultural identity in Indonesia and integrating cultural values into a multi-ethnic society increasingly open to globalization.